(untitled) (Law Research Review Quarterly, 2025)
This study addresses the legal uncertainty surrounding the term limits of legislative members in Indonesia, encompassing the House of Representatives (DPR), Regional Representative Council (DPD), and Regional People’s Representative Councils (DPRD). The core problem lies in existing laws, such as Law No. 17 of 2014 on MD3 and Law No. 8 of 2012 on Elections, which specify a five-year term but lack explicit limitations on re-election periods. This regulatory vacuum enables incumbents to hold office indefinitely, leading to significant implications for democratic quality. The research aims to analyze the legal and socio-political consequences of this unlimited tenure, including the stagnation of democratic circulation, the proliferation of political dynasties, increased risks of corruption, and declining public trust. It employs a normative-legal methodology, scrutinizing primary legal materials, academic journals, and survey data to evaluate the existing framework. Findings reveal that the absence of term limits undermines equal political opportunities, fosters political dynasties, and correlates with a high incidence of corruption cases among legislative members. Comparative analysis with other countries, such as Venezuela and the Philippines which impose strict term limits, highlights the necessity for reform. The study concludes that amending the 1945 Constitution and revising the MD3 Law and Election Law to include clear term limitations is crucial. These legislative reconstructions are essential to foster leadership regeneration, enhance accountability, and ensure a healthy, responsive constitutional democracy in Indonesia.